Analisis Pengaruh Cash Ratio, Return On Assets, Growth, Firm Size, Debt to Equity Ratio Terhadap Dividend Payout Ratio : ( Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2011) - Marietta, Unzu; Sampurno, Djoko (Faculty of Economics and Business Diponegoro University, 2013)
Manufacturing firm is processing industry company go through raw material into a goods. There are phenomenon in 2009 which showed that variable cash ratio, Return On Assets, size increased but it is not followed by increase Dividend Payout Ratio.This research aims to analyze the effect mechanism of liquidity, profitability, growth, firm size and financial leverage against the dividend payout ratio at manufacturing companies listed on the Indonesia stock exchange (IDX) for the period 2008-2011. The mechanism of liquidity determined by variable cash ratio, the mechanism of profitability described by variable return on assets, while financial leverage in this research described by variable debt to equity ratio. The sample used in this study 29 companies listed on the Indonesian stock exchange (IDX) for the period 2008-2011. Method of samples conducted by using purposive sampling. This research using multiple regression analysis including descriptive statistic test, classic assumptions test, and goodness of fit test. The result of this research showed that cash ratio had positive and not significant influence to dividend payout ratio, return on assets and size simultaneously had positive and significantly influence to dividend payout ratio, Growth was negative and not significant influence to Dividend Payout Ratio, meanwhile Debt to Equity Ratio had positive and significant influence to the Dividend Payout Ratio. Based on the coefficient of determination ( R2 ), having results of 0,224. It means independent variable influences the Cash Ratio, ROA, Growth, Size of the dependent variables, DER DPR can be described by this equation of 22,4%. While the rest of 77.6% is explained by other factors that are not included in the regression model.